Hyperkalemia and Metabolic Acidosis Occur at a Higher eGFR in Sickle Cell Disease. Issue 4 (28th April 2022) - Saraf, Santosh L.; Derebail, Vimal K.; Zhang, Xu; Machado, Roberto F.; Gordeuk, Victor R.; Lash, James P.; Little, Jane
Key Points: Hyperkalemia and metabolic acidosis are more common in severe and moderate sickle cell disease compared with age- and sex-matched African Americans from the National Health and Nutrition Examination Survey (NHANES). Hyperkalemia and metabolic acidosis occur at higher eGFR thresholds in sickle cell disease compared with age- and sex-matched African Americans from the NHANES. Visual Abstract: Abstract : Background: People with sickle cell disease (SCD) have an elevated estimated glomerular filtration rate (eGFR) compared with the general population, and this may alter the usual creatinine-based eGFR cutoffs for which physiologic evidence of kidney dysfunction is apparent. This study aimed to identify eGFR thresholds for hyperkalemia and metabolic acidosis in patients with SCD. Methods: This was a cross-sectional analysis of 733 patients with severe (hemoglobin SS or S β 0 -thalassemia) SCD genotype, 238 patients with moderate (hemoglobin SC or S β + -thalassemia) SCD genotype, and 1333 age- and sex-matched African Americans from the National Health and Nutrition Examination Survey (NHANES). The prevalence rates of hyperkalemia and metabolic acidosis were compared by eGFR category. Cutoffs for hyperkalemia and metabolic acidosis were determined using generalized additive models. Results: Hyperkalemia and metabolic acidosis were more common in those with severe SCD genotype (13% and 21%, respectively) compared with the NHANES (0.3% and 5%, respectively); the prevalence rates in the moderate SCD genotype were intermediate for hyperkalemia (3%) and metabolic acidosis (11%). The proportion of patients with hyperkalemia and metabolic acidosis progressively increased with lower eGFR category in both SCD genotype groups. The eGFR thresholds for hyperkalemia and metabolic acidosis were higher in the severe (85 and 91 ml/min per 1.73 m 2, respectively) and moderate (52 and 102 ml/min per 1.73 m 2, respectively) SCD genotypes compared with the NHANES (34 and 46 ml/min per 1.73 m 2 ). Conclusions: We demonstrate that hyperkalemia and metabolic acidosis are more common and occur at higher eGFR values in patients with SCD compared with age- and sex-matched African Americans, including in eGFR ranges considered to be normal. Future studies using redefined creatinine-based eGFR thresholds for abnormal kidney function may identify high-risk patients for earlier intervention strategies and referral for specialized renal care in SCD.